Efektivitas penambahan tepung jahe merah dalam ransum terhadap bobot potong, bobot karkas, dan presentase karkas burung puyuh jantan umur 6 minggu - Magdalena Siregar; Putra Utama Hia Siregar (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2023)
This study aimed to determine the effectiveness of adding red ginger meal to the ration on slaughter weight, carcass weight, and carcass percentage of 6-week-old male quail. This research was conducted in the Experimental Field of HKBP University, Nommensen, Medan. Two hundred male quail aged 1-6 weeks were randomly separated into four treatments and five replications so that each replication contained 10 quail. The four additional doses of the red ginger meal were 0% (P0 as a control), 0.75% (P1), 1.5% (P2), and 2.25% (P3). The research was carried out for 30 days to determine the impact on slaughter weight, carcass weight, and carcass percentage. The data obtained were analyzed using ANOVA and further tested using the Duncan Multiple Range Test (DMRT). The results showed that all observed variables did not show significant differences (P>0.05). However, adding 1.5% red ginger meal to the male quail's ration revealed a tendency for better results than other treatment doses. It can be concluded that adding red ginger meal to the male quail's ration is quite safe and has not been proven to impact carcass quality negatively.